Good Governance, Civil Society and Islam - Maszlee Malik (IIUM, 2015)
In post-modern times, there has been much empirical evidence to indicate that religions and faiths play a pro-active role in the field of civil society but more importantly in the development of societies, which is a major factor in political and economic development of a country, as well as its governance. Hence, explorations of religion and faith to develop an alternative notion of ‘good governance’ from ‘other’s’ worldview are also necessary. This book is an attempt to explore how Islam could play its functional role to create a sustainable governance concept based on values and ethics. It will look into the feasibility of some Islamic concepts that relates to governance, and how it fits into the framework of the modern day notion of ‘good governance’ through the realm of citizen politics, civil societies and NGOs. Readers will be introduced to some Islamic philosophical concepts derived from Islamic epistemology such as Tawhid, Amanah, Islah and others that will be explained in modern framework of good governance, to explore the viability of the relation between religion and governance.